An Upside-Down Logic-Based Neutrosophic Methodology: Assessment of Online Marketing Effectiveness in E-Commerce Enterprises - Yantao Bu (Neutrosophic Sets and Systems)
Online marketing plays a central role in the growth and competitiveness of e-commerce enterprises. However, evaluating its performance remains a complex task due to the presence of conflicting indicators, unpredictable user behavior, and shifting contextual factors. Standard evaluation models, which rely on fixed logic and linear metrics, often fall short of capturing the multi-layered realities of digital marketing environments. This paper proposes a novel framework that combines Upside-Down Logic with Neutrosophic Methodology to better interpret the effectiveness of marketing efforts. By integrating the dimensions of truth, falsity, and indeterminacy, the approach enables a more accurate representation of real-world scenarios where data signals can be ambiguous or contradictory. A case study of a mid-sized e-commerce business was developed to apply this methodology over a six-month simulated campaign period. Key marketing indicators including click-through rates, conversion, and retention—were analyzed using a neutrosophic model and logical transformations. These tools allowed for scenario-based interpretations that reflect changes in context, timing, and audience response. The outcomes highlight the limitations of traditional performance analysis and demonstrate how this logic-based model uncovers deeper insights. Campaigns that appear ineffective under conventional metrics may reveal hidden value when viewed through a more dynamic and flexible lens. The paper contributes to both theoretical understanding and practical strategy development in digital marketing, especially in environments characterized by uncertainty and non-linear behavior.